Agreed Fundamental Rules Relating to Contrast and Weighting, Diligence and Advisory Opinion, and their Jurisprudence Applications - Isteti, Mohammad Shareef Mustafa (European Scientific Journal, ESJ, 2019)
This paper focuses on addressing agreed fundamentals between fundamentalists, relating to contrast and weighting, diligence and advisory opinion with an explanation of each vocabulary base, the statement of the overall meaning, and the jurisprudence application to each rule. Basically, four rules were stated in this paper. This paper has shown that there were agreed fundamentals between fundamentalists. Hence, this serves as an alert to students of Shari school when reading fundamentalist rules, so as to be able to distinguish between what was agreed and what was disagreed. In addition, this paper contributes to the development of jurisprudential talent of students of Islamic Sharia through explaining the vocabularies of the rules, the statement of their meaning, and the jurisprudential applications on the fundamentalism rules.